Harnessing autophagy: A potential breakthrough in digestive disease treatment - EŞREFOĞLU, MUKADDES; Eşrefoğlu M. (My University, 2024)
Autophagy, a conserved cellular degradation process, is crucial for variouscellular processes such as immune responses, inflammation, metabolic andoxidative stress adaptation, cell proliferation, development, and tissue repair andremodeling. Dysregulation of autophagy is suspected in numerous diseases,including cancer, neurodegenerative diseases, digestive disorders, metabolicsyndromes, and infectious and inflammatory diseases. If autophagy is disrupted,for example, this can have serious consequences and lead to chronic inflammationand tissue damage, as occurs in diseases such as Chron\"s disease and ulcerativecolitis. On the other hand, the influence of autophagy on the development andprogression of cancer is not clear. Autophagy can both suppress and promote theprogression and metastasis of cancer at various stages. From inflammatory boweldiseases to gastrointestinal cancer, researchers are discovering the intricate role ofautophagy in maintaining gut health and its potential as a therapeutic target.Researchers should carefully consider the nature and progression of diseases suchas cancer when trying to determine whether inhibiting or stimulating autophagyis likely to be beneficial. Multidisciplinary approaches that combine cutting-edgeresearch with clinical expertise are key to unlocking the full therapeutic potentialof autophagy in digestive diseases
Keywords: Autophagy; Digestive disease; Gastrointestinal cancer; Harnessing autophagy; Inflammatory bowel disease